GAMBARAN KADAR KOLESTEROL, ALBUMIN DAN SEDIMEN URIN PENDERITA ANAK SINDROMA NEFROTIK - Handayani, Irda; Rusli, B.; Hardjoeno, Hardjoeno (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2007)
Nephrotic syndrome (NS) is characterized by proteinuria, hypoalbuminemia accompanied by oedema and hypercholesterolemia.Nephrotic syndrome is an often relapsing disease (75%) and often the diagnosis is too late. This disease is 15 times greater in childrenthan in adult and the male to female ratio is 2:1. Laboratory examination is needed to rapidly detect and evaluate the progress of thedisease for treatment. To know the distribution of NS based on aged, gender, cholesterol, and albumin concentration and the urinesediment profile. The data in this retrospective descriptive study were collected from 56 patients with NS at the Wahidin SudirohusodoHospital, Makassar, in the period of January 2004 – June 2006. NS were found in 36 male patients (64.3%) and 20 female patients(35.7%). Cholesterol concentrations were 250 mg/dl in 50 patients (89.3%) and 250 mg/dl in 6 patients (10.7%). Albuminconcentration was 2.5 g/dl in 21 patients (37.5%) and < 2.5 gr/dl in 35 patients (62.5%). In urine sediments, there were found in 23patients (41.1%) with positive proteinuria (+++), 51 patients (91.1%) with positive erythrocytes, 54 patients (96.4%) with positiveleucocytes, and 33 patients (58.9%) with positive cylinders such as rugged granular and fatty cost. More NS were found in male patientsin comparison to female, and many were aged + 6 years. Hypercholesterolemia, hypoalbuminemia, proteinuria, hematuria, leucocyturia,and positive cylinder (rugged granular and fatty cast) were found in the urine of most of the NS patients.